Potential Value of Serum Uric Acid in the Identification of Postoperative Delirium in Geriatric Patients Undergoing Knee Replacement - Wang, Fei; Tang, Xinhui; Wang, Jiahan; Liu, Siyv; Wu, Xiaoyue; Dong, Rui; Lin, Xu; Wang, Bin; Bi, Yanlin (Frontiers in Aging Neuroscience, 2022)
Objectives The relationship between preoperative serum uric acid (SUA) and cerebrospinal fluid (CSF) Alzheimer-related biomarkers were investigated to determine whether high SUA is a potential risk factor for postoperative delirium (POD) and to evaluate its predictive efficacy. Methods The participants were selected from the Perioperative Neurocognitive Disorder Risk Factor and Prognosis (PNDRFAP) study and the Perioperative Neurocognitive Disorder and Biomarker Lifestyle (PNDABLE) study. The logistic regression equation was used to analyze the risk factors and protective factors of POD. The interaction term (SUA × Sex) was introduced into the linear model to explore the potential modification effects of sex on the identified correlations. We analyzed the mediating effects of Alzheimer-related biomarkers. Finally, we constructed the receiver operating characteristic (ROC) curve and the nomogram model to evaluate the efficacy of SUA and Alzheimer-related biomarkers in predicting POD. Results Patients with POD had elevated SUA level (PNDRFAP: p = 0.002, PNDABLE: p < 0.001). Preoperative SUA level was positively correlated with CSF phosphorylated tau (P-tau) (p = 0.027) and β-amyloid42 (Aβ42)/P-tau (p = 0.023). Interaction analysis did not find any modification effect of sex. The relationship between SUA and POD was partially mediated by CSF P-tau (15.3%). ROC curve showed that the model combining SUA and Alzheimer-related biomarkers had better performance in predicting POD [area under the curve (AUC) = 0.880; p < 0.001], and the predictive model is accurate. Conclusions High SUA may enhance CSF P-tau level, thus increasing the risk of POD, and the model combining SUA and Alzheimer-related biomarkers can accurately predict the occurrence of POD.